The Practicing Workshop: A Development Project - Johansen, Guro Gravem; Nielsen, Siw Graabræk (Frontiers in Psychology, 2019)
In music academies and conservatoires, the culture of teaching and learning seems to nurture individuality and hierarchic structures at the cost of collaboration and sense of community. This could indicate a privatised conception of teaching and learning musical skills. As current research suggest that students’ learning may benefit from collaborative learning with their peers, the present article addresses music performance students’ understanding of the learning potential from participating in a specific social learning context. The study investigated students’ perceptions of outcomes from participating in a practising workshop in a music academy, on both an individual and social level. The workshop aimed at helping music performance students develop their understanding of instrumental practicing. The course allowed for sharing ideas and experiences, and for collaborative exploration, discussion and reflection. We conducted qualitative interviews with five volunteering students that had followed the workshop. Although identifying direct outcomes of the workshop in general proved to be difficult, we found that the students reported positive learning experiences from planning, implementing and presenting their individual development projects, and that their awareness of variations in the group strengthened their confidence in how they tailored their own individual practising. However, they also described more mixed outcomes in relation to learning about practising directly from other students. The study also revealed that just providing a group forum for students does not in itself lead to positive learning experiences. Implications of the study are discussed.